Two-Photon Polymerization of Sugar Responsive 4D Microstructures - Florea, Larisa; Trimble, Daniel; Delaney, Colm (My University, 2023)
Stimuli-responsive hydrogels have attracted much attention owing to the versatility of their programmed response in offering intelligent solutions for biomimicry applications, such as soft robotics, tissue engineering, and drug delivery. To achieve the complexity of biomimetic structures, two photon polymerization (2PP) has provided a means of fabricating intricate 3D structures from stimuli-responsive hydrogels. Rapid swelling hydrogel microstructures are advantageous for osmotically driven stimuli-response, where actuation speed, that is reliant on the diffusion of analytes or bioanalytes, can be optimized. Herein, the flexibility of 2PP is exploited to showcase a novel sugar-responsive, phenylboronic acid-based photoresist. This offers a remarkable solution for achieving fast response hydrogel systems that have been often hindered by the volume-dependent diffusion times of analytes to receptor sites. A phenylboronic acid-based photoresist compatible with 2PP is presented to fabricate stimuli-responsive microstructures with accelerated response times. Moreover, microstructures with programmable actuation (i.e., bending and opening) are fabricated using the same photoresist within a one-step fabrication process. By combining the flexibility of 2PP with an easily adaptable photoresist, an accessible fabrication method is showcased for sophisticated and chemo-responsive 3D hydrogel actuators.
PUBLISHED
Keywords: 4D printing; Responsive structures; Sugar responsive; Boronic acid; Microstructure; Nanoscience & Materials; Next Generation Medical Devices; Organic chemistry; Polymers; Polymers